Upaya meningkatkan hasil belajar melalui penggunaan lembar kerja peserta didik pada mapel IPS (Geografi) Kelas VII di SMPN 1 - Yuliana Yuliana; Suherdiyanto Suherdiyanto; Novita Sariani (LPD IKIP PGRI Pontianak, 2022)
This study aims to determine the improvement of student learning outcomes through the use of Student Worksheets (LKPD) in the seventh grade Social Sciences (geography) folder at SMP Negeri 1 Sungai Betung, Bengkayang Regency. This research is a classroom action research with two cycles. Each stage of the cycle includes planning, implementation, observation and reflection. The techniques used in this research consist of observation techniques, measurement techniques, and documentation. The data collection tool in this study used observation, test and documentation guides. The population and sample in this study were all students of class VIIE of SMP Negeri 1 Sungai Betung, Bengkayang Regency with a total of 33 students. Sources of data obtained from the results of tests and observations to be analyzed quantitatively and qualitatively. Based on the results of this study, it was shown that the implementation of learning using student worksheets for class VIIE students of SMP Negeri 1 Sungai Betung, Bengkayang Regency which was carried out by researchers in collaboration with social science subject teachers for class VII according to the Learning Implementation Plan (RPP) used 2 cycles. Each stage of the cycle includes planning, implementation, observation, and reflection. A learning implementation plan is made so that it can be carried out as planned in the learning implementation plan. It is known that in the first cycle the average value of student learning outcomes in social studies subjects is 48.96 with classical mastery of students 36.36%. From the results of the research and obtained the highest score of 73 and the lowest score of 16. And students who achieved the Minimum Completeness Criteria (KKM) were 12 people and students who did not reach the KKM were 21 people. While the treatment of cycle II had an average value of student learning outcomes in social studies subjects, namely 67.21 with classical completeness of students 78.78%. The highest score was 83 and the lowest score was 43. Of the students who achieved the Minimum Completeness Criteria (KKM) as many as 26 and 7 other students were still below the KKM. This shows that through the use of LKPD shows that the value of student learning outcomes has increased, this can be seen in the percentage of student learning mastery in the first cycle of 36.36% with an average value of 48.96, in the second cycle the percentage of student learning mastery has increased. to 78.78% in the successful category, in the second cycle there was an increase of 7.81. So, it can be concluded that the use of Student Worksheets (LKPD) can improve student learning outcomes for class VIIE SMP Negeri 1 Sungai Betung, Bengkayang Regency.